The Development of Innovation and Technology Utilization in Education: A Comparative Study of Finland, Japan, Singapore, and Indonesia - Ninuk Watini; Dina Wardani; Titin Andriyani; Adi Asmara (Gayaku Publisher, 2026)
Post-pandemic global educational digital transformation often falls into a hardware-oriented approach, neglecting educators' pedagogical readiness. This study aims to analyze and compare the policies, implementations, challenges, and successes of educational technology utilization in Finland, Japan, Singapore, and Indonesia. Utilizing a Systematic Literature Review (SLR) guided by the PRISMA protocol, this study analyzes 32 reputable scientific articles and national policy reports spanning from 2020 to 2026. The comparative analysis reveals three distinct approach patterns among the developed nations: Finland excels in research-based adaptive integration and teacher autonomy (pedagogy-first); Japan accelerates massive gigabit infrastructure through the GIGA School Program (technology-first); and Singapore systematically fuses both via an AI-powered centralized learning portal (systemic integration). Meanwhile, Indonesia demonstrates a digital leap through its Merdeka Belajar ecosystem (PMM and Belajar.id) but remains hindered by extreme infrastructure disparities in 3T regions. It is concluded that educational technology effectiveness depends on aligning teachers' pedagogical competence, digital infrastructure, and curricular flexibility. This study recommends restructuring teacher training based on the TPACK framework and accelerating digital network equity in Indonesia.